Distribution and population density of the ghost crab, Ocypode cursor (Linneaus, 1758) in Yumurtalik Beach, Turkey - (:unkn) unknown (Asian Journal of Agriculture and Biology, 2014)
The distribution and population density of the ghost crab, Ocypode cursor were studied in Yumurtalik Beach, Turkey during summer, 2009. Burrow densities of ghost crab were measured at three beach zones in relation to the Reference Datum (RD) with middle heights of 2, 4, and 9 m, which were located at medi-olittoral, supra-littoral, and sub-terrestrial fringe, respectively. Generally, individuals occurred above 1 m in height in relation to RD and peaked between 2 and 4 m. A range from 0 to 4.2 burrows/m2 was obtained, and the total number of crabs on this beach (approximately is 2256 km2) ranging from 18.99 burrows/m2 to 56.41 burrows/m2. Significant differences in the mean burrow density were found among three zones. Low densities were recorded in the sub-terrestrial zone in September and peak density in the supralittoral zone in August. In general crabs followed a clumped dispersion on Yumurtalik beach. In total 986 burrow diameters were measured where diameter ranged from 3 to 97.8 mm. The results provided evidence that Yumurtalik Beach can provide suitable habitats for O. cursor population. Ocypode cursor is not vulnerable to the anthropogenic disturbances and environmental alterations found at Yumurtalik Beach.
Keywords: Burrows; Density; Ghost crab; Ocypode cursor; Turkey; Yumurtalik Beach; Zonation